2019
DOI: 10.1177/0300060519837103
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan as a new force in the treatment of sepsis-induced cardiomyopathy: mechanism and clinical application

Abstract: The heart is one of the organs most vulnerable to sepsis. This review describes the general characteristics of sepsis-induced cardiomyopathy and the main pathogenesis of myocardial dysfunction in sepsis. Levosimendan is a novel drug for treatment of sepsis-induced myocardial dysfunction. This review also elaborates on the pathogenesis of levosimendan, including the mechanisms of its anti-inflammatory effects, improvement of myocardial ischaemia, increased synthesis of nitric oxide, vascular endothelial cell pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 43 publications
0
16
0
1
Order By: Relevance
“…Sepsis-induced myocardial injury triggers apoptosis in myocardiocytes via the mitochondrial pathway [17]. Apoptotic markers such as bax, bcl-2 and caspase-3 are central to mitochondrial function and any alteration in their expression levels will always result in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis-induced myocardial injury triggers apoptosis in myocardiocytes via the mitochondrial pathway [17]. Apoptotic markers such as bax, bcl-2 and caspase-3 are central to mitochondrial function and any alteration in their expression levels will always result in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Підвищення тропоніну зустрічається у 43-85 % хворих з септичним шоком та асоційоване з вищою летальністю [16]. З експериментальних робіт відомо, що порушення функції міокарда при сепсисі розвивається, незважаючи на достатню міо кардіальну перфузію та адекватне постачання кисню [11,21]. Основними механізмами ушкодження міокарда вважають вплив запальних цитокінів та ендотоксинів і дисфункцію мітохондрій [16].…”
Section: неішемічне ушкодження міокардаunclassified
“…In 2006, Rabuel and Mebazaa [ 44 ] concluded that approximately 15% of patients needed cardiotonic therapy to improve systemic circulation perfusion. As cardiotonic drugs, milrinone and levosimendan [ 45 47 ] are preferred. Catecholamines for sympathetic nerve excitation are not an option, which may have some connection with the stress explanation of LVSD in sepsis patients up to a point.…”
Section: Left Ventricular Systolic Dysfunction Vs mentioning
confidence: 99%